2010
DOI: 10.1186/1471-2458-10-639
|View full text |Cite
|
Sign up to set email alerts
|

Association of waterpipe smoking and road traffic crashes

Abstract: BackgroundThe purpose of this research was to examine whether waterpipe smokers experience increased risk of motor vehicle crashes.MethodsIn a telephone survey, a random sample of Iranian drivers were asked to report their age, gender, vehicle age, whether their vehicles were equipped with anti-lock braking system (ABS), average daily drive time (DDT), whether they smoked cigarette or waterpipe, whether they had diabetes mellitus (DM), number of traffic crashes during the last calendar year and whether the cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…In the present study, women with a university education were more likely to smoke a water pipe similar to previous studies [4,28], most probably due to peer pressure [5,6,26]. Considering the fact that people find many friends at their university, it may follow that students smoke a water pipe as a way of spending their leisure time, and this may account for the higher prevalence of water pipe smoking among people with a university education.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, women with a university education were more likely to smoke a water pipe similar to previous studies [4,28], most probably due to peer pressure [5,6,26]. Considering the fact that people find many friends at their university, it may follow that students smoke a water pipe as a way of spending their leisure time, and this may account for the higher prevalence of water pipe smoking among people with a university education.…”
Section: Discussionsupporting
confidence: 91%
“…Different regions designate the water pipe by different names, such as nargile , hookah, shisha , hubbly-bubbly, hubble-bubble, oriental pipe, boory , glase base, goza and mada’a . In Iran, it is known as ghalyan [3,4]. Misunderstandings about the dangers and complications of water pipe smoking are common.…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence rate of RTC in this study was similar to population based estimates in Iran [23]; therefore, the sample included in this study could be considered a representative sample of Iranian drivers. Drivers of ABS equipped vehicles reported less RTCs due to brake failure compared to similar vehicles that were not equipped with ABS.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, the study revealed that duration of daily driving and smoking were positively correlated with crashes. However, the year of manufacture of the vehicle was not associated with RTCs (109). Moreover, it was found that the proportion of drivers involved in RTCs decreased over the course of time from 15.90% in the first year of obtaining a driver’s license to 3.13% after 10 years of driving experience (88).…”
Section: Resultsmentioning
confidence: 99%